Elevated Levels of Anti-oxLDL Antibody in Relation with Acute Myocardial Infarction - Tserendavaa, Sumiya; Choi, Jung Rae; Malchinkhuu, Munkhzol (Central Asian Journal of Medical Sciences, 2021)
Objectives: We aimed to determine the serum level of anti-oxLDL antibody at the involving of acute myocardial infarction. Methods: In the case-control study, patients with acute myocardial infarction (coronary stenosis > 85%) as determined by quantities coronary angiography in the case group (n = 26) and healthy people with carotid artery stenosis (< 0.7 mm) have been involved in the control group (n = 50). We determined Anti-oxLDL antibody and oxLDL titers by ELISA. Results: Anti-oxLDL antibody levels for the case group were greater than the control group (p < 0.01). Using binary logistic regression, the anti-oxLDL antibody was significantly associated with acute myocardial infarction (OR = 1.082, p < 0.01). Conclusions: Elevated serum anti-oxLDL antibodies may be a risk factor for developing acute myocardial infarction and concerning the correlation of anti-oxLDL antibodies and acute myocardial infarction